Polymer microscopy - Sawyer, Linda C. (Springer, 2008)
Introduction to polymer morphology - Fundamentals of microscopy - Image formation in the microscope - Specimen preparation methods - Applications of microscopy to polymers - Emerging techniques in polymer microscopy - Problem solving summary - Appendices.